Sustainable Nanotechnology and Artificial Intelligence to Empower Image-Guided Therapy for Precision Healthcare - Drishya Prakashan; Ramya PR; Ajeet Kaushik; Sonu Gandhi (BME Frontiers)
Nanotechnology has substantially advanced imaging, therapy, and clinical techniques, playing a crucial role in the development of sustainable functional materials in biomedical engineering. Nanoparticles, used as contrast agents in multimodal imaging, offer notable advantages due to their high surface area-to-volume ratio, enabling functionalization with targeting ligands for improved specificity and sensitivity. They can also carry multiple imaging agents or therapeutic drugs, promoting theranostics, an approach combining diagnosis and treatment. However, the need for high-dose contrast agents raises concerns about nanoparticle toxicity. Green nanotechnology addresses this by developing sustainable nanoparticles through eco-friendly synthesis methods, reducing environmental and health risks. Moreover, by using this method, safer imaging agents that align with current health standards can be generated. In parallel, recent advancements in artificial intelligence (AI) are transforming imaging applications. Beyond simple automation of image interpretation, AI is enhancing image acquisition, management, and interpretation, signaling a future where intelligent systems play a key role in healthcare. This review explores the diverse nanomaterials utilized as contrast agents in multimodal imaging, highlights the importance of green nanotechnology in minimizing toxicity, and emphasizes on the important role of AI in imaging and image-guided therapy. Together, these innovations are advancing precision healthcare, promising a future where diagnostics and treatment are not only more effective but also sustainable.